NILAI-NILAI BUDAYA SUNDA DALAM PERMAINAN ANAK TRADISIONAL DI DESA SINDANGKERTA KECAMATAN CIPATUJAH KABUPATEN TASIKMALAYA - Saepudin, Encang; Damayani, Ninis A. (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2016)
This study examines the Kaulinan Budak Lembur (Sundanesse village children traditional games) preservation model in Sindangkerta District of Cipatujah Tasikmalaya. With qualitative methods and techniques of collecting data through interviews, observation, focus group discussions, and the literature study,thes study aims to identify the type of game, the values contained in the game, and the preservation of the children games in Sindangkerta District of Cipatujah Tasikmalaya. Respondents in this study are managers of Saung Budaya Tatar KarangCipatujah and village community leaders of Sindangkerta. The results of this research show that there are twelve type of games that is preserved by Sindangkerta community. Every game has a life values applied by the mutual love, mutual teaching, and mutual care (silih asih, silih asah, dan silih asuh). The values in the game are togetherness, leadership, honesty, tolerance, moderation, etc.